Nursing care at the end of life : what every clinician should know - Lowey, Susan E.; Open SUNY Textbooks; BC Open Textbook Project; BCcampus (Open SUNY Textbooks, 2015)
"Nursing Care at the End of Life: What Every Clinician Should Know should be an essential component of basic educational preparation for the professional registered nurse student. Recent studies show that only one in four nurses feel confident in caring for dying patients and their families and less than 2% of overall content in nursing textbooks is related to end-of-life care, despite the tremendous growth in palliative and end-of-life care programs across the country. The purpose of this textbook is to provide an indepth look at death and dying in this country, including the vital role of the nurse in assisting patients and families along the journey towards the end of life. There is an emphasis throughout the book on the simple, yet understated value of effective interpersonal communication between the patient and clinician. The text provides a basic foundation of understanding death and dying, including a brief historical examination of some main conceptual models associated with how patients cope with impending loss. An overview of illness trajectories and models of care, such as hospice and palliative care are discussed. Lastly, the latest evidence-based approaches for pain and symptom management, ethical concerns, cultural considerations, care at the time of death, and grief/bereavement are examined. The goal of this text is to foster the necessary skills for nurses to provide compassionate care to individuals who are nearing the end of life and their families. Every chapter contains a "What You Should Know" section which highlights and reinforces foundational concepts."--BC Campus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on online resource; title from pdf title page (viewed on May 18, 2016).
Keywords: Nursing -- Textbooks; Electronic books